Intravenous infusion-related nosocomial infections in children - M. Hardjono ABdoerrahman; Pingkan Palilingan; Taralan Tambunan; S. Harry Purwanto (Paediatrica Indonesiana, 1999)
A prospective study was conducted ID obtain the basic data of intravenous infusion-related nosocomial infections at the Pediatric Department Child Health, Cipto Mangunkusumo Hospital in Jakarta during the period of March - May 1998. Subjects were patients with a single intravenous infusion without any other invasive measures. All patients were admitted at the intermediate and ordinary ward that was classify tothe First and Second Class, Third Class according to room rate and number of beds. From 62 patients with intravenous infusion, 21 were infected (33. 9% with 95%CI; 0.226; 0.471). Complications of intravenous infusions were skin infdtrations (17 /62), phlebitis (8/62), bacteremia (4/62), and septicemia (1/62). The most frequently foundmicroorganism were Staphyloroccus epidermidis, Enterobacter aerogenes, Acinobacter calroaceticus, Serratia marcescens, Pseudomonas aeruginosa and Staphylococcus aureus. The results of the senstivity tests of those microorganisms proved that all bacteriac, Gram positive as well as Gram negative were sensitive to the followingantibiotics (in decreasing order): cypronoxacine, amikacin, gentamicin, cefphyrome and ceftriaxon. Gram positive bacteriae were also sensitive to vancomycin and cephalotin.